A selenophene substituted double-cable conjugated polymer enables efficient single-component organic solar cells. Issue 8 (29th January 2020) - Yu, Peiting; Feng, Guitao; Li, Junyu; Li, Cheng; Xu, Yunhua; Xiao, Chengyi; Li, Weiwei
Abstract : Double-cable conjugated polymers with selenophene substituted conjugated backbones were developed for single-component organic solar cells with an efficiency of 6.25%. Abstract : In this work, a selenophene based double-cable conjugated polymer has been developed for application in single-component organic solar cells (SCOSCs). When incorporating selenophene into the conjugated backbones, the new double-cable polymer exhibited a red-shifted absorption spectrum, a high-lying frontier energy level and good crystallinity. The polymer as a single photo-active layer was applied in SCOSCs, providing a high efficiency of 6.25% with a high photocurrent of 12.68 mA cm −2, which is among the highest performance in SCOSCs. We further studied the nanophase separation of the selenophene based double-cable polymer, revealing that the planar and crystalline conjugated backbones caused poor crystalline cooperativity between the conjugated backbones and side chains containing electron acceptors. This could explain the relatively low fill factor in SCOSCs due to the possibly strong charge recombination.